Retrospective assessment of parental attitudes versus severity of early maladaptive schemas in a non-clinical population of Polish adults – preliminary reports - Talarowska, Monika; Juraś-Darowny, Małgorzata (Current Problems of Psychiatry, 2024)
Objectives: While from a developmental perspective, a secure bond with a parent is of great importance to a child's functioning, its establishment depends mainly on the caregivers and their parental attitudes – specific strategies or styles that enable the fulfilment of parental responsibilities. The objective of the presented study was to assess the correlation between the early maladaptive schemas and retrospectively assessed parental attitudes.Methods: The study involved 94 people between the ages of 18 and 64 (average age: M=34.84, SD=11.12). Each participant completed a set of the following tools: the Young Schema Questionnaire (YSQ-S3-PL), the Parent-Child Relationship Questionnaire (PCR), and the Young Parent Inventory (YPI).Both parents’ attitudes were similarly associated with the formation of early maladaptive schemas. For both mothers and fathers, loving and rejecting attitudes had the most numerous associations with the formation of early maladaptive schemas.Conclusions: 1. In a retrospective evaluation of the subjects, both parents had a similar impact on the formation of domains of early maladaptive schemas.The Results: only statistically significant differences occurred in the domain of Impaired Autonomy and Performance. Mothers had a stronger influence on the formation of schemas in this group. 2. For both mothers and fathers, loving (L) and rejecting (R) attitudes had the most numerous associations with the formation of early maladaptive schemas.